EMOTIONS IN THE WORKS OF F.S. FITZGERALD’S “THE GREAT GATSBY” - Astanbekova Sabohat Sultonbek qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotatsiya: The Great Gatsby is a story about the impossibility of recapturing the past and also the difficulty of altering one’s future. The protagonist of the novel is Jay Gatsby, who is the mysterious and wealthy neighbor of the narrator, Nick Carraway. Although we know little about Gatsby at first, we know from Nick’s introduction—and from the book’s title—that Gatsby’s story will be the focus of the novel. As the novel progresses and Nick becomes increasingly drawn into Gatsby’s complicated world, we learn what Gatsby wants: Daisy, Nick’s cousin, the girl he once loved. Anything and anyone that stands between Gatsby and Daisy becomes an antagonist. Although Daisy’s brutish husband Tom is the most obvious antagonist, a variety of more abstract concepts—such as class difference, societal expectations, and Gatsby’s past lies—can also be considered antagonists. The most powerful antagonist is time itself, which prevents Gatsby from recapturing what he lost. This article analyses some other sides which emotions used in this work.